Phosphorescent Vapochromic Responses of Copper(I) Complex Bearing Pyrazole Ligands for Detection of Alcohol Derivatives - Nur Fatiha Ghazalli; Nurul Husna Sabran; Juan Matmin; Mohamad Azani Jalani; Hendrik O. Lintang (Penerbit UTM Press, 2024)
Indexed by WOS/Scopus/MyCite